Electric Canting Innovation for Production Cost Efficiency in Randu7 Mulia Batik SMEs Probolinggo - Wilamsari, Feni; Hariyanto, Moh. Fendi; Ferdiansyah, Nanda Bagus; Cahyono, Budi Dwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This research presents an effort to innovate electric canting by utilizing the micro heater element in solder (MHE), where MHE is active when it receives electricity. MHE acts as an element that converts electrical energy into heat, and with a relatively stable temperature, MHE can heat the malam liquid storage tube. The hot malam tube will be filled with solid malam until the malam melts and can be applied to cloth. In addition, an on off button is also installed which functions to transmit and cut off electricity to the MHE or in other words adjusts to user needs. The implementation of the use of electric canting started at Batik Randu7Start and then it can also be implemented at other hand-written batik SMEs in Probolinggo. The benefits of this electric canting aside from overcoming the problems that exist in UMKM Batik Randu7, what is no less important is being able to reduce production costs when compared to using manual canting. With this, it is also hoped that MSMEs can continue to grow batik and create competitive advantages in the market.